Thermal Stability of Peroxy Acyl Nitrates Formed in the Oxidation of CxF2x+1CH2C(O)H (x = 1,6) in the Presence of NO2 - Henao Arboleda, Diana Patricia (2013)
The formation of CxF2x+1CH2C(O)OONO2 (x = 1,6) from the photooxidation of CxF2x+1CH2C(O)H (x = 1,6) in the presence of NO2 was investigated. The infrared spectrum of C6F13CH2C(O)OONO2 is reported for the first time, and thermal stability for both peroxynitrates at 295 K and 9.0 mbar is informed. Kinetic parameters (activation energy and pre-exponential factor) for CF3CH2C(O)OONO2 at 9.0 and 1000 mbar are: 108 ± 2 kJ/mol, 1.5 × 1015 and 114 ± 2 kJ/mol, 2.4 × 1016, respectively. A comparison is made between fluoro and hydrogenated peroxy acyl nitrates.